2010
DOI: 10.3109/15368378.2010.493129
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Geomagnetic Field in Cell Regulation

Abstract: We advance the hypothesis that biological systems utilize the geomagnetic field (GMF) for functional purposes by means of ion cyclotron resonance-like (ICR) mechanisms. Numerous ICR-designed experiments have demonstrated that living things are sensitive, in varying degrees, to magnetic fields that are equivalent to both changes in the general magnetostatic intensity of the GMF, as well as its temporal perturbations. We propose the existence of ICR-like cell regulation processes, homologous to the way that bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…To understand the process more completely, it is necessary to focus on possible changes of cellular and molecular regulation in accordance to local Earth time varying magnetic field (TVMF) strength changes. It is already known that isolated animal cells have specific sensitivity to the strength and frequency of fluctuation of the TVMF [4][5][6]. The TVMF regulatory effect proposed to be associated with the ion cyclotron resonance mechanism [5] whose effect on extracted myocardial cells has been recently demonstrated under laboratory conditions [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the process more completely, it is necessary to focus on possible changes of cellular and molecular regulation in accordance to local Earth time varying magnetic field (TVMF) strength changes. It is already known that isolated animal cells have specific sensitivity to the strength and frequency of fluctuation of the TVMF [4][5][6]. The TVMF regulatory effect proposed to be associated with the ion cyclotron resonance mechanism [5] whose effect on extracted myocardial cells has been recently demonstrated under laboratory conditions [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is already known that isolated animal cells have specific sensitivity to the strength and frequency of fluctuation of the TVMF [4][5][6]. The TVMF regulatory effect proposed to be associated with the ion cyclotron resonance mechanism [5] whose effect on extracted myocardial cells has been recently demonstrated under laboratory conditions [7]. Scientists have shown that healthy people in isolation from the magnetic field (MF) significantly increases their capillary blood flow and reduces the diastolic blood pressure [8].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of electromagnetic field action in live systems has been extensively discussed earlier (Al Ghamdi, 2012;Goodman et al, 1993;Kohane and Tiller, 2000;Lednev, 1991;Liboff, 1985Liboff, , 2009Liboff, , 2010Liboff and McLeod, 1988;Panagopoulos et al, 2000Panagopoulos et al, , 2002Panagopoulos et al, , 2013Panagopoulos, 2012;Vincze et al, 2008). They proposed that such fieldinduced resonance effects may be attributed to (i) medium polarization, (ii) charged particle motion in the medium; and (iii) charged particles moving through the membrane channels.…”
Section: Discussionmentioning
confidence: 95%
“…(Liboff, 2007), clinical treatment of non-unions and spinal fusion in bone (Liboff, 2006), ion parametric resonance (Blanchard and Blackman, 1994;Lednev, 1991;Vincze et al, 2008), aminoacid conductivity (Alberto et al, 2008a,b;Comisso et al, 2006;Del Giudice et al, 2002;Pazur, 2004;Zhadin et al, 1998), protein hydrolysis (Novikov and Fesenko, 2001) and stem cell differentiation (Gaetini et al, 2009). As noted by Liboff (2010), one possibility to understand EMF phenomenon is that the frequency must be specifically tuned to the unhydrated ion. However, it is quite difficult to imagine the presence of such ions in aqueous solutions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation